The Role of Literacy in Creasing Awareness of Waste Management - Wulandari, Silvia Dwi (SERUNAI, 2022)
This research aimed to analyze the role of literacy in increasing awareness of waste management. This research utilized a qualitative method. The results indicated that addressing waste management issues also requires the integration of technology. Digital media usage significantly influences the shift in individuals' mindsets. Enhancing waste literacy can be achieved through social media platforms. Educational initiatives can leverage various features provided by these platforms. Tailoring educational approaches to the age group of the target audience is crucial for effective information delivery. Merely providing education and knowledge is insufficient to cultivate self-awareness among individuals. It would be advantageous if education is complemented by tangible actions, such as community service, outreach programs, and training sessions. These activities should be customized to suit different age groups and environments.